2004
DOI: 10.1021/jo030342y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Studies of the Properties of a Liquid-Crystalline Quaterrylenebis(dicarboximide) by 1H NMR and UV−vis Spectroscopies

Abstract: The synthesis of an ionic quaterrylenebis(dicarboximide) 1a, a long-wavelength absorbing mesogen, is described. When compared with its analogue 2a, an ionic perylenebis(dicarboximide), the aromatic protons of 1a exchange with deuterium of concentrated D(2)SO(4) at a dramatically faster rate. In addition, stronger aggregation in aqueous media was observed for 1a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…The vessel was inserted into the microwave reactor (Discover, CEM Corp.) and irradiated at different temperatures, power settings, and for various time durations. Due to the poor solubility of some PDCIs, the reaction yield is determined from the isolation yield after the train sublimation (entry [4][5][6][8][9][10]. The reactions of substituted anilines or amines were studied next to determine their reactivities (Table I).…”
Section: Results and Discussion Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The vessel was inserted into the microwave reactor (Discover, CEM Corp.) and irradiated at different temperatures, power settings, and for various time durations. Due to the poor solubility of some PDCIs, the reaction yield is determined from the isolation yield after the train sublimation (entry [4][5][6][8][9][10]. The reactions of substituted anilines or amines were studied next to determine their reactivities (Table I).…”
Section: Results and Discussion Synthesismentioning
confidence: 99%
“…[9] Although the reaction yield is reasonable, between 45-62%, this procedure might not be suitable for some aryl substituted imides, owing to their poor solubility in acid and basic solutions. A typical synthesis of PDCIs required multiple synthetic steps and used perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) as the starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Our next challenge was to find efficient approaches with the goal of accomplishing the ring-closure reaction. As a matter of fact, the last cyclization reaction was performed under different conditions such as (1) KOH in ethanol with glucose; 23 (2) t-BuOK/DBN in diglyme; 24 (3) FeCl 3 in nitromethane and dichloromethane; 25 and (4) K 2 CO 3 in ethanolamine. 26 It was found that the first three methods all failed and complicated mixtures were obtained probably due to the decomposition of NPDI units.…”
Section: Rylenesmentioning
confidence: 99%
“…© Thieme Stuttgart • New YorkSynlett 2012,23,[171][172][173][174][175][176][177][178][179][180][181][182][183][184] …”
unclassified
“…However, this requires com-parably rough reaction conditions. Some improvements were obtained with the combination of KOH/glucose, 11,12 however, with varying results and a special treatment of the reaction products is required.…”
mentioning
confidence: 99%